The Effectiveness of Collaborative Learning in Chemistry: An Analysis of Students' Perceptions, Self-Confidence, and Motivation - Munawwarah Munawwarah; Zuhra Adminira Ruslan (Jurnal Pelita: Jurnal Pembelajaran IPA Terpadu, 2025)
The urgency of this research lies in the pressing need to gain an in-depth understanding of how collaborative learning, particularly through group work and presentations, influences students’ self-efficacy and motivation within the context of 21st-century chemistry education. This study examined students' perceptions of collaborative learning in chemistry, specifically group work and presentations, and explored their relationship to self-efficacy and motivation. This study employed a mixed-methods design. The participants consisted of 30 first-year undergraduate students enrolled in an introductory chemistry course. They were selected using a convenience sampling technique. The main instrument used in this study was a questionnaire. Data analysis was carried out in two complementary stages, namely quantitative analysis and qualitative analysis. Descriptive statistics showed that students' overall perceptions of collaborative learning were quite positive, with a mean score of 3.69 on a 5-point scale. Among the five dimensions, interaction and collaboration (M = 3.74) and fairness and accountability (M = 3.73) received the highest ratings, while presentation (M = 3.53) received the lowest. The perception scale demonstrated good reliability with a Cronbach's Alpha of 0.82. Thematic analysis of qualitative responses revealed that group work was perceived as beneficial for understanding complex material through peer explanations, but challenges such as uneven contributions and limited preparation time persisted. Students' self-efficacy increased with adequate preparation and mastery of the material, but was often hampered by nervousness and fear of making mistakes during presentations. Motivation was found to stem from intrinsic factors, such as curiosity and interest in chemistry, as well as extrinsic factors, including grades, recognition, and classroom atmosphere. Students also provided constructive suggestions for improving collaborative learning, such as clearer role assignments, more structured guidance, and fairer assessments. These findings suggest that while collaborative learning in chemistry has great potential, its effectiveness depends on addressing organizational and psychological aspects.